Programs to improve neighborhoods. Reflections about its fundamentals and the pertinence of its objetives in base of the analysis of PROMEBA (Argentina) and its implementation in the city of Resistencia, Chaco - Romagnoli, Venettia (2006)
Fil: Romagnoli, Venettia. Universidad Nacional del Nordeste. Facultad de Arquitectura y Urbanismo; Argentina.